Are invasive species promoting yellowjacket invasion in Patagonia? - Masciocchi, Maite; Villacide, Jose Maria; Buteler, Micaela; Martinez Von Ellrich, Andres (Wiley, 2023)
In recent decades, yellowjacket wasps, including Vespula vulgaris, have successfully been established in Patagonia. Additionally, the invasive willow Salix fragilis has also invaded areas next to watercourses, which in turn are typically colonized by the giant willow aphid (GWA, Tuberolagnus salignus), another invasive species. The honeydew exuded by the aphids has been reported to be used as a carbohydrate source by this social wasp. Our aim was to determine whether willows and GWA (invasive complex) on the stream shores promotes yellowjacket population growth. We worked under the hypothesis that GWA provides honeydew (i.e. carbohydrates) to yellowjackets, favouring nest growth and individual fitness. Our results indicate that habitats close (<200 m) to stream margins, where S. fragilis and GWA occur, contain not only a greater abundance of workers but also a higher nest density of V. vulgaris yellowjackets. Even though the nests were similar in size irrespective of the distance to the stream, weight, size and nutritional status of individuals suggest that foraging/nesting in proximity of the invasive complex promotes larger and better nurtured wasps, including reproductive castes, that in the long run could drive population growth and spread of the species in Patagonia. In this context, our study suggests that management of V. vulgaris populations should adopt strategies that encompass a broad approach, especially adopting new strategies designed to contemplate relevant multitrophic interactions between yellowjackets and invasive willows and aphids.